ChemInform Abstract: An Unusual Glycosylation Product from a Partially Protected Fucosyl Donor under Silver Triflate Activation Conditions. Issue 17 (28th April 2014) - Daly, Robin; Scanlan, Eoin M.
Abstract The partially protected fucosyl donor (I) is activated in the presence of primary alcohols (II) to give unexpected difucoside products (III) exclusively.